Debt, Dividend Policy, Taxes, Inflation, and Market Valuation: Erratum - Modigliani, Franco (Journal of Finance, 1983)
The following is A correction to The Presidential Address published in the Journal of Finance 37 (May 1982). It first arises in Equation II.1 (p. 258) and results from the fact that, in computing the (real) return from the ith share, I failed to subtract the tax on the nominal capital gain accruing to that share as a result of inflation, namely: τ g m p S i . Accordingly, this quantity should be added with a negative sign in the curly bracket in the first equality of II.1, and in the square bracket in the second equality in II.1 as well as in II.2. Unfortunately this error turns out to affect a good many of the equations, though its magnitude seems small enough so as not to require significant revisions of any major conclusions. Accordingly, and to save space, I will report specific corrections for some basic formulae and only indicate the nature of required changes in most others. Thus, l* can still be put at about 1 / 3 of l when p is zero, but tends to rise relative to l with inflation. Finally, I am glad for this opportunity to correct a serious omission in the list of acknowledgements in the first footnote of the paper, namely that of Richard Cohn, whose painstaking review of the manuscript was invaluable.